Análisis histórico e interpretativo de la Suite Iberia de Isaac Albéniz (2016)
Abstract. The present paper shows in detail the structural analysis, harmonic analysis and other musical characteristics that make up the twelve pieces of one of the most important works of the piano literature of all times, as well as the composer's biographic context given its importance in the understanding of his compositional style.